Korelasi antara Pengelolaan Sistem Informasi Sekolah dengan Efektivitas Kerja Pegawai di SMK Hasanuddin Mataram - Menik Aryani (LPPM Universitas Pendidikan Mandalika, 2015)
The purpose of this research was to determine the correlation between school management information system and work effectiveness of staff at SMK Hasanuddin Mataram. The method of data gathering used questionnaire and interview. The data were analyzed statically by using correlation product moment. The results indicated that, r-table equals to 0,311, r-test at the significance level of 5% with N=48 It was obtained 0,248 this shows that r- test is bigger than r-table or 0,311>0,248, thus the result of this research is significant. This means H0 is rejected and Ha is accepted. Hence, it can be concluded that there is a correlation between school management information systems and work effectiveness of staff at SMK Hasanuddin Mataram.